Phronesis and the Precautionary Principle in the Context of Practices Associated with Big Data - Zárate Sánchez, Roberto (2025)
Introduction. This research examines the relationship between the precautionary principle and Aristotelian phronesis in the context of practices associated with Big Data, aiming to analyze their theoretical and practical relevance. This analysis is situated within the framework of new humanism, which seeks to critically reflect on contemporary human activities and their ethical orientations. Methodology.To achieve this purpose, a narrative literature review is conducted, guided bythe definition of three key categories: phronesis, precautionary principle, andBig Data. Results. It is possible to establish a clear theoretical relationship,particularly drawing from philosopher Marcos (2018), between phronesis and the precautionary principle. Additionally, considering the challenges posed by BigData—such as the commodification and instrumentalization of data, algorithmicdiscrimination, privacy issues, and the presence of logical biases in analysis—phronesis and the precautionary principle are deemed relevant. Conclusions. It can be concluded that the precautionary principle and phronesis are pertinent to thepractice of Big Data and its associated processes, and their theoretical relationship is evident. However, it is important to note that there are many practical limitations to their implementation, including the predominance of deontological approaches, dynamics based on instrumental rationality, and varying political contexts. This article is structured in five parts: an introduction that outlines the research problem,key background information and justification, focused on the article’s connection to new humanism; the methodology, the theoretical framework centered on the previously mentioned categories, the analysis of the results from the narrative literature review and, finally, the conclusions.